2014
DOI: 10.1103/physreve.89.033308
|View full text |Cite
|
Sign up to set email alerts
|

Strong plastic deformation and softening of fast colliding nanoparticles

Abstract: Nanoparticles, with sizes ranging between 1 and ∼102 nm, show dynamical properties distinctly different than those of bulk materials. Due to their large surface area to volume ratio, their properties often depend on length scales. We investigate the size and the collision velocity (vcoll) dependence of the coefficient of restitution (COR) for nanoparticles made of a face-centered cubic lattice of Lennard-Jones atoms via nonequilibrium molecular dynamics simulations. A sharp crossover between elastic collision … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 30 publications
2
39
0
Order By: Relevance
“…While v c does not exhibit any explicit size dependence, it has of course been reasoned that the materials properties -and here in particular the yield strength -may depend on size, leading to an increase of v c for smaller NPs. We note, however, that in a recent study of LJ NPs oriented such that the meet with their (100) facets Takato et al [27] found a larger macroscopic value of v c = 0.16 based on Eq. Furthermore, we note that due to the small size of the NPs the collisions occur at a high strain rate,ǫ ∼ v/R, which may reach values of up to 0.1 for our smallest NPs.…”
Section: B Existing Models For Critical Velocitymentioning
confidence: 52%
See 1 more Smart Citation
“…While v c does not exhibit any explicit size dependence, it has of course been reasoned that the materials properties -and here in particular the yield strength -may depend on size, leading to an increase of v c for smaller NPs. We note, however, that in a recent study of LJ NPs oriented such that the meet with their (100) facets Takato et al [27] found a larger macroscopic value of v c = 0.16 based on Eq. Furthermore, we note that due to the small size of the NPs the collisions occur at a high strain rate,ǫ ∼ v/R, which may reach values of up to 0.1 for our smallest NPs.…”
Section: B Existing Models For Critical Velocitymentioning
confidence: 52%
“…Because of the simplicity of the setup, NP collisions have been frequently studied, and results on the restitution coefficient [25], NP bouncing off a surface or off other NPs [26,27], grain mixing [28], fragmentation [29,30], and the occurrence of inelastic processes [31] have been reported. Because of the simplicity of the setup, NP collisions have been frequently studied, and results on the restitution coefficient [25], NP bouncing off a surface or off other NPs [26,27], grain mixing [28], fragmentation [29,30], and the occurrence of inelastic processes [31] have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…MD simulation is now a reliable numerical method to examine mechanical properties of oxide glasses owing to valuable efforts to develop accurate interatomic potentials. [11][12][13] In addition, improving of computational performance enables one to simulate not only simple deformations but also more realistic conditions to mimic mechanical experiments, such as indentation, [14][15][16] scratch [17][18][19][20] and impact, 21,22 for example. Many studies have also shown that MD can capture crack propagation in nanoscale.…”
Section: Introductionmentioning
confidence: 99%
“…In face-centered cubic (fcc) lattice materials there are four {111} slip planes and three 110 slip directions in a unit cell [3]. Small nanoparticles of a single fcc crystal colliding in the {100} direction also show the slip deformation of the crystal in numerical simulations [4]. Once dislocations are nucleated, they propagate until reaching the free surface.…”
Section: Introductionmentioning
confidence: 99%